2023
DOI: 10.1038/s41598-022-27252-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct components of cardiovascular health are linked with age-related differences in cognitive abilities

Abstract: Cardiovascular ageing contributes to cognitive impairment. However, the unique and synergistic contributions of multiple cardiovascular factors to cognitive function remain unclear because they are often condensed into a single composite score or examined in isolation. We hypothesized that vascular risk factors, electrocardiographic features and blood pressure indices reveal multiple latent vascular factors, with independent contributions to cognition. In a population-based deep-phenotyping study (n = 708, age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…Finally, we sought external validation of the HDM3 parameters. In previous work (King et al, 2023), we estimated three latent vascular factors (LVFs) from six potential measures of vascular health in the CamCAN dataset. These factors corresponded roughly to total blood pressure (LVF1), pulse pressure (LVF2) and heart rate variability (LVF3), shown to be associated to cerebrovascular health measures in the CamCAN cohort (Fuhrmann et al, 2019; Tsvetanov et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we sought external validation of the HDM3 parameters. In previous work (King et al, 2023), we estimated three latent vascular factors (LVFs) from six potential measures of vascular health in the CamCAN dataset. These factors corresponded roughly to total blood pressure (LVF1), pulse pressure (LVF2) and heart rate variability (LVF3), shown to be associated to cerebrovascular health measures in the CamCAN cohort (Fuhrmann et al, 2019; Tsvetanov et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Research suggests a positive correlation between fluid and crystallized intelligence in cognitively normal adults [ 13 , 14 ]. However, as individuals age, crystallized abilities appear to remain stable or even show improvement [ 15 ], unless cognitive impairment or dementia sets in [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disparity between fluid and crystallized intelligence serves as a predictive factor for abnormal cognitive decline. Fluid intelligence experiences significant deterioration compared to crystallized intelligence [ 14 ], and it also leads to the development of compensatory aging theories [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Looking into specific cognitive functions, a large study conducted by Crichton et al revealed an association between visual-spatial memory, working memory, scanning and tracking, executive function, and cardiovascular health [ 15 ]. More generally a study by King et al found that there is an overproportioned decline in fluid relative to crystallized intelligence in the presence of cardiovascular risk factors [ 16 ]. Reduced brain perfusion and chronic low-grade inflammation due to CVD risk factors are discussed as possible pathophysiological links [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%